Analysis of Media Exposure Effects on Introducing Sports Tourism Events: A Case Study of The 23rd Tour de Borobudur 2023 - Calvin Zefanya; Wiga Nurlatifa Romadhoni; Billy Castyana; Tandiyo Rahayu; Dewangga Yudhistira (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
Media exposure is an essentials in introducing the sports tourism event in the digital era, such as Tour de Borobudur 2023 event which is annually held in Central Java. Media exposures have important role in attracting people, although it is rarely mentioned which media and what platforms is the most suitable and effective in introducing sports tourism event, this research aiming to seek the best type of media platform to introduce the Tour de Borobudur event. A qualitative with exploratory research design is used to finds the results, which is resulting in 18 (July) & 25 (August) publications in 2 months for the online media. Social media overall ER percentage is 6,26%, with the ER of Instagram is 9,6 %. Social media exposure rate is categorized having high exposure (Benchmark ER >2%), with instagram platform being the most effective and relevant social media based on ER ( Benchmark ER >6%) to gain exposure in introducing Tour de Borobudur 2023 sport tourism event. It is proven by the data that social media is the best type of media and Instagram is the most suitable platform to give the exposures towards the introducing of Tour de Borobudur event.